Life cycle assessment of fermentative production of lactic acid from bread waste based on process modelling using pinch technology - Vanapalli, Kumar Raja; Bhar, Rajarshi; Maity, Sunil K.; Dubey, Brajesh K.; Kumar, Sandeep; Kumar, Vinod (Elsevier, 2023)
Bread waste (BW), a rich source of fermentable carbohydrates, has the potential to be a sustainable feedstock for the production of lactic acid (LA). In our previous work, the LA concentration of 155.4 g/L was achieved from BW via enzymatic hydrolysis, which was followed by a techno-economic analysis of the bioprocess. This work evaluates the relative environmental performance of two scenarios - neutral and low pH fermentation processes for polymer-grade LA production from BW using a cradle-to-gate life cycle assessment (LCA). The LCA was based on an industrial-scale biorefinery process handling 100 metric tons BW per day modelled using Aspen Plus. The LCA results depicted that wastewater from anaerobic digestion (AD) (42.3–51 %) and cooling water utility (34.6–39.5 %), majorly from esterification, were the critical environmental hotspots for LA production. Low pH fermentation yielded the best results compared to neutral pH fermentation, with 11.4–11.5 % reduction in the overall environmental footprint. Moreover, process integration by pinch technology, which enhanced thermal efficiency and heat recovery within the process, led to a further reduction in the impacts by 7.2–7.34 %. Scenario and sensitivity analyses depicted that substituting ultrapure water with completely softened water and sustainable management of AD wastewater could further improve the environmental performance of the processes.
Keywords: Lactic acid; Bread waste; Life cycle assessment; Sensitivity; Uncertainty; Pinch technology